The Role of Transformative Technologies in Enhancing the Quality of Nursing Care During the COVID-19 Pandemic - Kia-Rostami, Nahid (Global journal of Business and Integral Security, 2024)
The COVID-19 pandemic has imposed unprecedented challenges on healthcare systems, and nursing care quality has become a focal point of concern. This paper aims to evaluate the pivotal role of transformative technologies in enhancing the quality of nursing care during the ongoing pandemic. The results provide insights into nurses’ adoption and utilization of digital tools and platforms to mitigate the unique challenges posed by COVID-19. Telemedicine, a cornerstone of these technologies, has enabled healthcare professionals to provide remote consultations and monitor patients, reducing exposure and improving access to care. Additionally, electronic health records have facilitated seamless information sharing among healthcare providers, enhancing care coordination and reducing errors. Telemonitoring technologies have empowered nurses to remotely observe patient vital signs and symptoms, allowing for early intervention and personalized care plans. Furthermore, wearable devices and mobile applications have promoted patient engagement and self-management, reinforcing the patient-nurse partnership. In conclusion, transformative technologies have revolutionized nursing care quality during the COVID-19 pandemic, which expanded the nursing role in healthcare delivery and strengthened the ability to adapt to dynamic challenges. These technologies remain essential for keeping nursing care patient-centered, efficient, and safe throughout the pandemic.